IMPACT THE USE OF LMS ON TEACHER PERFORMANCE IN POST- PANDEMIC HYBRID LEARNING AT SMAN 2 WAWO - M. Ali Sadikin; Hermawansyah; Nurhasanah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Post-pandemic, the use of Learning Management Systems (LMS) to facilitate hybrid learning has become increasingly popular. This tool helps teachers at SMAN 2 Wawo manage a blend of online and in-person instruction. A qualitative descriptive methodology was used, and data was collected through document review, observation, and interviews. According to research findings, learning management systems (LMS) facilitate resource organization, increase student engagement, and simplify evaluation procedures. Benefits for students include faster feedback, more opportunities for self-directed learning, and flexibility in accessing learning resources. However, challenges remain, such as inadequate infrastructure, varying levels of instructor digital literacy, and limited internet access. While further optimization requires infrastructure support and instructor capacity building, LMSs are a crucial tool that can help make hybrid learning practices more flexible, adaptable, and student-centered